2006
DOI: 10.1002/rem.20092
|View full text |Cite
|
Sign up to set email alerts
|

Ex situ treatment of MTBE‐containing groundwater by a UV peroxide system

Abstract: This article describes the design, implementation, and operating results for an ex situ ultraviolet/hydrogen peroxide (UVP) system to treat methyl tert-butyl ether (MTBE) in extracted groundwater. The UVP modification was designed to reduce the operation and maintenance costs of an existing groundwater pump-and-treat treatment system that relied on air stripping and carbon adsorption. The UVP system is relatively inexpensive and can easily be scaled to cope with different groundwater extraction rates up to 80 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Whereas, the rate constants of SO 4 −• with HPO 4 2− and H 2 PO 4 − are 1.2 × 10 6 and 7× 10 4 M −1 s −1 . 37 Maruthamuthu and Neta 37 found that SO 4 −• may react with phosphate anions to propagate a chain reaction and form various phosphate radicals, the oxidation potentials of which were all less than SO 4 −• .…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 93%
See 2 more Smart Citations
“…Whereas, the rate constants of SO 4 −• with HPO 4 2− and H 2 PO 4 − are 1.2 × 10 6 and 7× 10 4 M −1 s −1 . 37 Maruthamuthu and Neta 37 found that SO 4 −• may react with phosphate anions to propagate a chain reaction and form various phosphate radicals, the oxidation potentials of which were all less than SO 4 −• .…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 93%
“…3 Ex-situ treatment with a UV peroxide system is an efficient and effective technology for contaminated groundwater remediation. 4 The UV/H 2 O 2 process is also a technique used in the treatment of chlorinated solvent contamination in groundwater based on the generation of the highly reactive hydroxyl radical with a standard redox potential of 2.70 V. Trichloroethene (TCE) is proved to be completely degraded by UV/H 2 O 2 processes. 5 However, chlorinated alkanes are more resistant to UV/H 2 O 2 processes than alkenes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation